Interventions to enhance adherence to dietary advice for preventing and managing chronic diseases in adults: a study protocol - Gravel Karine; Ratté Stéphane; Lapointe Annie; Desroches Sophie; Légaré France; Thirsk Jayne (BMC, 2011)
Abstract Background Adoption of a healthy diet has been identified as the cornerstone in the prevention and management of chronic diseases. However, non-adherence to lifestyle changes raises an important issue since adherence level to dietary advice is a key determinant of the effectiveness of dietary treatment. Therefore, based on the results of a Cochrane systematic review on interventions for enhancing adherence to dietary advice for preventing and managing chronic diseases in adults, the aim of this study is to assess the importance and applicability of interventions enhancing adherence to dietary advice in the Canadian context. Methods/Design In phase 1, dietitians' opinion will be assessed through a Delphi study regarding the importance and the applicability in the Canadian context of the interventions found the most effective to enhance adherence to dietary advice through a Cochrane systematic review. In phase 2, findings of the Cochrane systematic review assessing the effects of interventions for enhancing adherence to dietary advice will be reported in a practical format on an online knowledge translation tool for dietitians and other health professionals. Discussion In recent years, there has been an increasing recognition of the failure to translate research findings into clinical practice. Therefore, knowledge translation efforts need to prioritize effective interventions that will be the most relevant for practice and end-users by adapting them to the local context. Our study will provide decision makers in the field of dietetic practice with essential knowledge on adherence for elaborating educational activities for academic or professional settings that will respond to dietitians' priorities in terms of importance and applicability to day-to-day practice.